Social welfare, interventionism, and indeterminacy: In defense of Rothbard - Wysocki, Igor; Dominiak, Łukasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
The present paper argues that Rothbard’s economic case against the state is more robust than suggested by his critics. The charge that it might be anemic is based on the suggestion that we can say literally nothing about the way governmental acts bear on social utility. Contra this supposition we submit that Rothbard’s critics missed the fact that the effects of governmental interventions might be actually indeterminate in two ways: weakly or strongly. If the indeterminacy involved in his welfare theory is weak, then his economic criticism of the state is more robust than envisaged by these authors. To the effect that this indeterminacy is indeed weak we advance the following reasons: Rothbard’s understanding of the Unanimity Rule; the avoidance of the contradiction allegedly committed by Rothbard over one and the same page of his famous essay; his economic criticism of interventionism being better aligned with his overall ethical anti-governmental stance; the principle of charitable reading, which cuts across all of the previously stated reasons. If our arguments count for something, then we are warranted in claiming that Rothbard is indeed able to say something about social utility under interventionism. And if so, then his criticism of interventionism should be viewed as robust rather than anemic.
Keywords: indeterminacy; interventionism; social welfare; Murray N. Rothbard; welfare